Rethinking economic growth - Cousins, Sean; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2001)
In this program, with the aid of colourful graphics, arresting footage, a young presenter and interviews with economists and federal politicians, attempt to sort out the debate over economic growth
Title from title screen
Executive producer, Neil Barrett ; camera, David Hudspeth ; music, Barry Palmer ; editor, Simon Wright
Presenter: Lisa Hickey
Keywords: Economic developmet; Development economics; International economic relations